Development of a 3d bioprinting system, characterisation of bioink and printing microspheroids of hela cells - Othman, Sheril Amira (2020)
In Malaysia, Industrialised Building System (IBS) has been recognised as a potential solution in improving the deliverables of construction projects. However, the acceptance of this modern technology is still low. Most of the construction players prefer the conventional construction method which leads to a longer duration, lower productivity and poor quality of the building. The adoption of IBS requires systematic project management to ensure the best output in improving construction deliverables. Improper IBS project management can generate physical and non-physical waste in the production and construction tasks. This research aimed to evaluate on how to prevent waste and any types of loss during IBS construction by implementing lean management. This research examined the relation between critical factors in implementing lean management technique using the Interpretative Structural Modelling (ISM) method. In establishing ISM model, 51 influencing factors in implementing lean management based on lean construction key principles had been identified throughout an extensive literature review. The results from questionnaire survey identified 18 critical success factors for lean management adoption in IBS application. For further investigation, semi-structured interviews were conducted to collect the qualitative data for the critical factors. ISM analysis method was used to study the association between each critical success factor. The initial model was developed to promote the adoption of lean management technique in IBS construction. Deeper ISM analysis established a Matrice d’Impacts Croisés Multiplication Appliqués à un Classement (MICMAC). The MICMAC results in this research demonstrated that four important factors are categorised as Independent / Driving factors namely ‘planning’, ‘educate labour’, ‘modularisation’, and ‘standardisation’. These factors were explored in detail to drive the performance elements categorised in Dependent factor which is ‘reduce production time’. The findings provide a model that prioritised the critical success factors which lead to framework of lean management application in IBS production.